2011
DOI: 10.1111/j.1439-0272.2010.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

CAG repeat length in androgen receptor gene and male infertility in Egyptian patients

Abstract: The CAG repeat and its association with infertility has been debatable. Therefore, this study was planned to assess the distribution of CAG repeat expansion in Egyptian patients and to investigate its association with male infertility. Forty-five infertile men were eligible for the study in addition to 20 aged-matched fertile males as control. Semen analysis, scrotal sonography, assay of serum testosterone, follicle-stimulating hormone (FSH) and luteinising hormone (LH), and determination of the CAG repeat num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
3
20
1
Order By: Relevance
“…Eventually, 41 English and 3 Chinese reports meet all criteria of inclusion. 1,12–28,31–37,39,40,42–49,5153,5658,61,62,64 The characteristics of the selected studies are shown in Table 1. One report 25 included studies on 2 different ethnic groups, so we consider it as 2 separate studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, 41 English and 3 Chinese reports meet all criteria of inclusion. 1,12–28,31–37,39,40,42–49,5153,5658,61,62,64 The characteristics of the selected studies are shown in Table 1. One report 25 included studies on 2 different ethnic groups, so we consider it as 2 separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…Data of azoospermic group were provided by 19 reports. 12–24,27,28,33,37,42,45 Six reports 13,17,25,32,61,62 provided data of oligospermic group without further stratification. Some reports 12,1416,18-21,23,24 classify oligospermic group according to sperm concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Relationship between the length of AR (CAG)n and current testosterone levels is somewhat inconsistent referring to the previous studies in males: The four studies indicate that the length is positively correlated with the levels (De Naeyer et al, ; Ma et al, ; Manuck et al, ; Stanworth, Kapoor, Channer, & Jones, ); another study, however, demonstrates a significant negative correlation between them (Mosaad, Shahin, Elkholy, Mosbah, & Badawy, ); and another 15 studies report there is no a significant correlation between them at all (Aluja et al, ; Durdiaková et al, ; Durdiaková et al, ; Eisenegger, Kumsta, Naef, Gromoll, & Heinrichs, ; Gettler et al, ; Goutou, Sakka, Stakias, Stefanidis, & Koukoulis, ; Hampson & Sankar, ; Kubranska et al, ; Lapauw, Goemaere, Crabbe, Kaufman, & Ruige, ; Nowak, Diamond, Land, & Moffat, ; Ryan et al, ; Sankar & Hampson, ; Schneider et al, ; Schneider, Zitzmann, Gromoll, Ladwig, & Berger, ; Stiger et al, ). Regarding the same relationship analyzed by previous studies for females, two studies indicate the length is positively correlated with the levels (Peng et al, ; Skrgatic, Baldani, Cerne, Ferk, & Gersak, ); such relationship, however, is significantly negative (Brum et al, ; Jaaskelainen et al, ); or not significant (Durdiaková et al, ; Jaaskelainen, Korhonen, Voutilainen, Hippelainen, & Heinonen, ; Nowak et al, ).…”
Section: Study 3: the Relationship Between Ar(cag)n With Current Testmentioning
confidence: 92%
“…The authors reported a negative correlation between CAG repeat length and sperm count thereby validating the concept that long stretches of CAG repeat may be associated with derangement of sperm production, presumably via decreased AR function. [4347] Data associating androgen receptor CAG repeats with prostate cancer have been inconsistent but several studies have linked variation in CAG repeat length to clinically aggressive CaP. [4852]…”
Section: Mechanisms That May Underlie the Association Between Male Rementioning
confidence: 99%